ANALISIS KONSEP PEMBELAJARAN MATEMATIKA BERBASIS MINDFUL LEARNING PADA SEKOLAH PUSAT KEUNGGULAN DI SMK NEGERI 5 DENPASAR - I Komang Sukendra; I Dewa Putu Juwana; I Kadek Juni Arta (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to analyze and evaluate the concept of mindful learning-based mathematics instruction at the Center of Excellence School, SMK Negeri 5 Denpasar. This study used a mixed methods approach that combines quantitative and qualitative analysis, involving teachers and students as respondents. The research instrument was a teacher and student questionnaire that underwent validity and reliability testing. The test results showed that all statement items had an r-value above 0.30 and a Cronbach's Alpha value above 0.90, thus declaring the instrument valid and reliable. The data analysis revealed that teachers had a positive perception of the implementation of mindful learning-based mathematics instruction, as it was considered capable of increasing student learning awareness, focus, and active engagement in the learning process. Meanwhile, the analysis of student questionnaires indicated that the mindful learning approach provided a more reflective learning experience, increased learning motivation, and helped students understand mathematical concepts more deeply. The findings of this study indicate that the concept of mindful learning-based mathematics instruction has the potential to improve the quality of mathematics instruction in vocational education and is relevant for implementation at SMK Negeri 5 Denpasar as a Center of Excellence School.